PERANCANGAN PROMOSI WAREHOUSE CLOTHING MELALUI MEDIA AUDIO VISUAL - MUHAMMAD ILHAM, Hendra Afriwan, S.Sn., M.Sn., Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Clothing Company is a term used for a company that produces apparel under the name of brand. first goods produced in the form of shirts, but as the development needs and customer demand, the product was expanded to pants, wallets, handbags and other accessories. Clothing Warehouse is one of the clothing company located in the city of Padang. Originated from the desire of the owners want to open a clothing company with the concept seriously but there is an element of cheerful finally materialized, the owner of the warehouse clothing is Farid Mohammed, clothing company was founded on January 20, 2015 which at that time was still hesitate to start this business because of lack of capital, but thanks to the support of family and friends this business was run. Because new clothing venture company, warehouse does not have a fixed promotional media, audio-visual equipment to facilitate the delivering and receiving materials, thoughts and messages as well as to avoid misunderstanding, and therefore the author makes a campaign for the warehouse by selecting the audio-visual media.Key word : Warehouse Clothing, Audio Visual.